2020
DOI: 10.11606/s1518-8787.2020054002263
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to pesticides and health symptoms among family farmers in Brazil

Abstract: OBJECTIVE: To explore the association of occupational pesticide exposure with acute and mental health symptoms. METHODS: Cross-sectional survey carried out with 78 Brazilian family farmers, who were pesticide applicators and helpers conveniently selected. Symptoms and exposure data were collected by interviews, and mental health outcomes by the Self-Reporting Questionnaire. Blood samples were analyzed to assess cholinesterase levels. Exposure indicators and symptoms were compared between applicators and helper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 23 publications
2
33
0
7
Order By: Relevance
“…Possible findings to explain part of these symptoms were related to the fact that they use fewer items of personal protection during the use of pesticides. In light of this, the need for surveillance actions, technical support, and safety training during occupational and environmental exposure to pesticides should be encouraged as a way to impact on the reduction of these causes, in order to decrease the outcomes related to suicidal behavior in farmers [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible findings to explain part of these symptoms were related to the fact that they use fewer items of personal protection during the use of pesticides. In light of this, the need for surveillance actions, technical support, and safety training during occupational and environmental exposure to pesticides should be encouraged as a way to impact on the reduction of these causes, in order to decrease the outcomes related to suicidal behavior in farmers [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies are yielding promising results and found that people experience some comfort in giving/receiving virtual spiritual support. However, better understanding is needed to explore and improve new accepted conceptions and practices around spiritual support provision that the current pandemic has started unlocking (Betz et al, 2019 ; Drummond & Carey, 2020 ; Ribeiro et al, 2020 ; Swift, 2020 ), including the virtualisation and modification of spiritual support, such as the key aspect of ″being there″, and new ways of ″dying well″ and providing holistic care in our fast evolving contemporary society.…”
Section: Discussionmentioning
confidence: 99%
“…The UK is one of the top twenty countries affected by COVID-19 worldwide, scoring fifth for number of cases and deaths; this implies that the burden of COVID-19 has been very high, with—at time of writing—over 61,200 deaths and many more sick people spending days, or weeks, of suffering and/or being ventilated artificially in intensive care before most of them dying (Johns Hopkins Coronavirus Resource Center, 2020 ). Both anecdotal accounts and evidence from available studies around spiritual care during COVID-19 emphasized the lack of spiritual support (Ferrell et al, 2020 ; Ribeiro et al, 2020 ; Roman et al, 2020 ), as well as the lack of preparedness within the healthcare systems, which were found not to be equipped to enable staff and spiritual service providers to respond to those in need.…”
Section: Introductionmentioning
confidence: 99%
“…Neste artigo, apresentam-se as frequências absolutas e relativas para subsidiar a discussão dos conhecimentos, experiências, atitudes e práticas, enquanto maiores detalhes sobre a metodologia do estudo (Leão et al, 2018), efeitos respiratórios (Buralli et al, 2018) e sintomas mentais e de intoxicação (Buralli et al, 2020) são apresentados em estudos anteriores.…”
Section: Métodosunclassified
“…Sobre quem recomendava os agrotóxicos que deveriam ser utilizados, 30 agricultores (39%) afirmaram ser os vendedores ou agrônomos, 15 (19%) disseram ser eles próprios, outros produtores ou os proprietários das lavouras e oito entrevistados (10%) disseram não saber. Cerca de 30% dos aplicadores não sabiam quais agrotóxicos utilizavam, em virtude de pulverizarem a mistura preparada por terceiros (Buralli et al, 2020). Sobre quem orientava as doses e frequência de aplicação, dos respondentes dessa pergunta (n=58), 29 entrevistados (50%) citaram os vendedores e agrônomos, 15 (26%) disseram ser eles próprios, outros produtores ou os proprietários e 14 (24%) afirmaram seguir o recomendado nas bulas e rótulos dos produtos.…”
Section: Tabela 1 -Continuaçãounclassified